Nutrition-Sensitive Irrigation and Water Management - Bryan, Elizabeth (World Bank, Washington, DC, 2019)
This document summarizes evidence and guidance on project design and results framework indicators for nutrition-sensitive irrigation and water management investments for which improving nutrition in vulnerable populations is a specific objective of the project. Drawing on the current body of evidence on the links between irrigation, water management, and nutrition through the pathways of production, income, women’s empowerment, and water and hygiene, the report describes eight nutrition-sensitive approaches for achieving greater impacts on early child nutrition. Results framework indicators are proposed to support monitoring and evaluation of nutrition-sensitive investments in water management and irrigation.